Modeling, Pedagogical Modeling and The Concept of Pedagogical Modeling of The Preparation of Future Teachers (Eurasian Research Bulletin, 2022)
The article illuminates the pedagogical interpretation of the problem of modeling and modeling. Definitions were studied given by teachers by teachers to pedagogical modeling, its components, types and methods of principles, a comparative analysis of the concepts of design and modeling was carried out. Based on scientific research, a model for the implementation of pedagogical training of future teachers has been developed.